A constitutive model incorporating grain refinement strengthening on metallic alloys. (20th October 2021) - Cao, Shan Cecilia; Zhang, Xiaochun; Yuan, Yuan; Wang, Pengyau; Zhang, Lei; Liu, Na; Liu, Yi; Lu, Jian
Abstract: Surface nano-crystallization techniques have been recently developed as one of the most effient ways to optimize materials' structure, and therefore develop the local and global mechanical behavior as to increase strength without compromising ductility. In this work, we present a constitutive model incorporating grain refinement hardening to simulate the nano-crystallization technique, specifically, surface mechanical attrition treatment. The computation is implemented using user-defined VUMAT subroutines. As an example of its application, a geometry model with full coverage of random impacts are employed. The results show that the model has rather precise predictability of grain size evolution during plastic deformation. The readily embedded with a computational code of material dynamics enables this novel model to be a promising tool to study the dynamic evolution of microstructures under plastic deformation.